Evaluation and comparison of sample homogenization and plating methods for raw meats and poultry - Jamora, Jennifer Rachel J.; Dumelod, Benelyn Domingo (1995.)
ABSTRACT This study was conducted to compare the efficiency of the stomacher and blender in sample homogenization. The other primary objective was to compare the efficiency of PetrifilmTM SM and PetrifilmTM CC versus that of conventional Plate Count agar and Violet Red Bile agar, respectively,in enumeration of aerobic bacteria and coliforms. PetrifilmTM is a relatively recent development-a portable, rehydratable, sample-ready system containing the nutrients of their conventional counterparts, plus indicator dyes to facilitate counting. A randomized complete block design was used in conjunction with a two-way analysis of variance for the log10 counts of aerobic organisms and coliforms in order o determine any significant differences homogenization methods, plating methods, and the interaction between the two. Correlation coefficients in the enumeration of aerobes were also calculated to determine the strength of linear relationships existing between homogenization or plating method. Results of the ANOVA for both aerobic and coliform counts for all samples proved that no significant differences existed between sample homogenization and plating methods. No interaction effects were found. Correlation was high for the media and homogenizers used in the aerobic plate count. The preceding results indicate that the stomacher and the blender, and PetrifilmTM and conventional media, are equally efficient homogenization and plating methods, respectively, in microbiological analyses.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Meat industry and trade -- Philippines